Factores asociados a un predictor de mortalidad en hemorragia digestiva alta en el Hospital Regional de Loreto, julio 2021 a julio 2022 - Almeida Hidalgo, Marco Tulio (2023)
Upper gastrointestinal bleeding is one of the frequently observed pathologies in the emergency department, which involves around 150 hospitalizations worldwide and mortality is related to the coexisting comorbidities of patients and their advanced age. The present investigation aimed to determine the factors associated with a mortality predictor in high gastrointestinal bleeding at the Regional Hospital of Loreto during the period from July 2021 to July 2022 using the AIMS65 scale. A descriptive, observational, cross-sectional, and retrospective study was conducted, where the medical records of adult patients hospitalized in the medicine service of the Regional Hospital of Loreto during the period from July 2021 to July 2022 were evaluated. A mortality rate of 10.5% was obtained with a statistically significant association with the use of the AIMS65 scale (p<0.05), male sex prevalence with 57.9% of the cases, hospital stay of more than 5 days with 75.4% of the cases, hypertension as the most frequent comorbidity with 42.1% of the cases. Melena as the most frequent clinical presentation with 71.9% of the cases, moderate and severe anemia with 31.6% and 38.6% of the cases, elevation of glucose in 57.9% of the cases, alteration of albumin values in 59.6% of the cases, and gastric ulcers as the most frequent endoscopic finding with 42.3% of the performed endoscopies. It was found that the level of education, Glasgow Coma Scale evaluation, creatinine measurement, Albumin, and INR have a statistically significant association with a High-Risk profile according to the AIMS65 scale to predict mortality in patients with Upper Gastrointestinal Bleeding. It is concluded that there are factors associated with the AMIS65 mortality predictor in patients with Upper Gastrointestinal Bleeding.